All-metal cavity antenna with light weight, high efficiency and circular polarization for satellite platform applications. (18th May 2023) - Luo, Yanbin; Zeng, Qingsheng; Xu, Guanghui; Chen, Shitao; Denidni, Tayeb A; Gao, Steven; Wang, Wei
Abstract: In this paper, a lightweight high-efficiency circularly polarized (CP) all-metal antenna design method is presented for satellite industry applications. The proposed antenna is composed of a rectangular waveguide feeder, a high-order mode cavity and a metasurface circular polarizer (MCP). The cavity high-order mode TE440 is directly excited by four coupling slots in the waveguide. The MCP is placed on the cavity to generate the CP radiation. Due to the introduction of high-order mode technology and MCP, all metal walls inside the antenna can be removed, which are necessary in conventional waveguide structures, and weight is thereby significantly reduced. To reflect the weight advantage, a conventional metal wall-loaded waveguide antenna of the same size is designed. The measured results show that the proposed antenna has wider impedance and axial ratio bandwidths, and higher radiation efficiency. In particular, the proposed antenna is 40% lighter than the comparative one, indicating that it is more applicable to satellite platforms with limited loading capacities.